Georgi Gospodinov’s Struggle with the Category of Time During the Crisis Period - Szwat-Gyłybowa, Grażyna (Poznańskie Studia Slawistyczne, 2022)
The article is devoted to a reflection on the category of time in Georgi Gospodinov’s novel Vremeubežiŝte (2020), where the author undertakes a reflection on the processes of culpable and non-culpable self-destruction of societies that have rejected the rules of Enlightenment rationalism. Using the tools of dystopia, he creates a world gripped by collective madness, the sources of which he derives from extra-literary reality and links to contemporary political and cultural processes. Leszek Kolakowski’s concept of time as the vault of the human home, which is based on four pillars: reason, God, love, death, remains the philosophical point of reference for my deliberations. In turn, the concept of retroutopia of the sociologist of culture Zygmunt Bauman provided me with tools to reflect on a new type of rationalism after the conservative turn. René Girard’s concept of mimetic competition was helpful in considering the structure of the world presented in the novel.